MORAL FILM MESSAGE ON WEB SERIES TEMAN KE SURGA - Debbie Pradhita; Panji Dwi Ashrianto; Yenni Sri Utami (The Indonesian Journal of Communication Studies, 2019)
Nowadays, the phenomenon of religious-themed films is increasingly emerging in Indonesia, because Indonesia is a country with the largest Muslim population in the world, making it one of the target markets for religious nuances. Film web series Teman ke Surga are interesting as learning media for religious moral values in the midst of the rise of television films, most of which are not in accordance with the teachings of Islam. The formulation of the problem in this research is how is the perception of the public in the Yogyakarta Regional Yuk Ngaji community towards the moral message in the web series film "Teman ke Surga". This study aims to find out the moral message in a friend's film series web to Teman ke Surga in detail the perceptions of the community of Yuk Ngaji about the moral message in web series Teman ke Surga. The theory used in this study is the uses and effect theory and perception theory. This type of research is qualitative research. The technique of collecting data uses observation, in-depth interviews and documentation. The results of this study indicate that web series films are an alternative medium in educating Muslims in accordance with Islamic law. In the Teman ke Surga web series the message conveyed is to hasten marriage in Islam, obedience to parents, Compliance with Wives Against Husbands. Informant perceptions interpret the Teman ke Surga web series film, which is about the rules of how teenagers do not delay in marriage when they are considered capable of getting married in Islam about how to solve every problem in marriage, how jurisprudence is recommended in developing husband and wife relations, how Islam forbids dating before marriage and obedience of wife to husband.